2023
DOI: 10.3390/asi6050089
|View full text |Cite
|
Sign up to set email alerts
|

Development and Future Trends of Digital Product-Service Systems: A Bibliometric Analysis Approach

Slavko Rakic,
Nenad Medic,
Janika Leoste
et al.

Abstract: As a plan, Industry 4.0 encourages manufacturing companies to switch from conventional Product-Service Systems to Digital Product-Service Systems. Systems of goods, services, and digital technologies known as “Digital Product-Service Systems” are provided to improve consumer satisfaction and business success in the marketplace. Previous studies have looked into various elements of this area for industrial companies and academic institutions. Digital Product-Service Systems’ overall worth and expected course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…In the context of Industry 5.0, Digital Product-Service Systems contribute to all three of the main approaches [24]. The contribution to human-centricity reflects in the number of people needed to successfully implement and manage the Digital Product-Service Systems, which enables improvement of the existing value chains and the creation of new ones [25,26].…”
Section: Digital Product-service Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of Industry 5.0, Digital Product-Service Systems contribute to all three of the main approaches [24]. The contribution to human-centricity reflects in the number of people needed to successfully implement and manage the Digital Product-Service Systems, which enables improvement of the existing value chains and the creation of new ones [25,26].…”
Section: Digital Product-service Systemsmentioning
confidence: 99%
“…Finally, during the COVID-19 pandemic, Digital Product-Service Systems proved to be resilient, precisely because of their digital aspects [24]. Digital services can be provided no matter the time and place, the main condition is to have Internet access so that the digital services can be delivered [29].…”
Section: Digital Product-service Systemsmentioning
confidence: 99%
“…The integration of digitalization and servitization is viewed as cutting-edge practice in the manufacturing industry, with digital servitization potentially reshaping production modes in the digital age. However, further clarification on digitalization and servitization is needed (Rakic et al, 2023;Chen et al, 2023).…”
Section: Research On the Digitalization Of Manufacturingmentioning
confidence: 99%
“…In the context of digital transformation, researchers have examined how the integration of digital technologies can enhance an organization's agility and adaptability. Studies have found that the use of cloud computing, big data analytics, and automation can enable businesses to quickly sense and respond to market changes, rapidly develop and deploy new products or services, and adapt their operations to evolving customer needs [64].…”
Section: Agility and Adaptability As Key Strategic Responses To Marke...mentioning
confidence: 99%